Effect of cooking methods and intestinal conditions on lipolysis, proteolysis and xanthophylls bioaccessibility of eggs. (July 2018) - Asensio-Grau, Andrea; Peinado, Irene; Heredia, Ana; Andrés, Ana
Graphical abstract: Highlights: Poaching led to the highest digestibility under exocrine pancreatic insufficiency (EPI). Boiling and poaching enhance bioaccessibility of lutein and zeaxanthin under EPI. Poached egg is advised for a better lipid digestion in eggs for individuals with EPI. Lipolysis, proteolysis and xanthophylls bioaccessibility are limited in omelette. Abstract: Digestibility of macro and micronutrients depends on the ingested food as well as on gastrointestinal conditions, being those suboptimal in exocrine pancreatic insufficiency (EPI) patients. Under this scenario, oral enzyme supplementation improves enzymatic hydrolysis of nutrients. In this study, a static in vitro model was used to assess lipids and protein digestibility as well as lutein and zeaxanthin bioaccessibility of eggs cooked differently and submitted to different intestinal conditions. Boiled, poached and omelette eggs were digested under different intestinal conditions of pH (6 or 7), bile concentration (1 or 10 mM) and doses of the enzyme supplement (1000–4000 LU/g fat). Results showed that poaching resulted in higher digestibility of lipids and proteins, compared to boiling or omelette preparations, under gastrointestinal conditions of EPI (pH 6, bile 1 mM). Concerning xanthophylls bioaccessibility, boiling and poaching led to higher bioaccessibility of lutein and zeaxanthin than omelette under EPI conditions.